Pellet group count methods to estimate red deer densities: precision, potential accuracy and efficiency - Alves, Joana (2018)
Pellet group count methods are key tools for wildlife conservation and management. Therefore, it is essential to clarify the performance and suitability of the different pellet group count methods at distinct realities. This issue has been discussed by other researchers but with inconsistent conclusions, leaving open the necessity of additional studies. Aiming to fill this need, we used a combination of field data and simulation models to evaluate the density estimates, precision and potential accuracy of the results obtained through each pellet group count method, and also the sampling effort and efficiency associated with them. The methods evaluated were standing crop plot counts (FSCP), clearance plot counts (FAR), standing crop strip transect counts (ST) and standing crop line transect counts (LT). Deer density estimates by the four methods were statistically similar at all effort levels simulated. The analyses of CV trends reveal a better precision supplied by FSCP than by FAR for the same effort, while ST and LT yielded comparable values in analogous situations. The time required to make a survey is a key factor in the choice of a field technique. LT with distance sampling was the most efficient method to count pellet groups, while FAR seems to be the less proficient method. Attending to the limitations usually inherent to field surveys, like time, technicians and budget, LT appeared more efficient than the other methods, providing great precision and accuracy in less time. Nevertheless, at high densities and pronounced habitat heterogeneity, FAR became more efficient than FSC, do not requiring the decay rates, allowing accurate estimates in a few months when applied with the proper effort and environmental conditions. This study highlights the importance of carrying out pilot studies and simulation models to evaluate the sampling design prior to its implementation in the field.